Effectiveness of the Dengue Hemorrhagic Fever (DHF) Control Program at Lhok Bengkuang Community Health Center, South Aceh - Husnul Fitri, Maghfiratul; Safrizal, Safrizal; Fahlevi, Muhammad Iqbal; Alamsyah, Teuku; Syahputra, Firman Firdaus; Din, Misbahud (PT.Mantaya Idea Batara, 2025)
Background: Dengue Hemorrhagic Fever (DHF) remains a significant public health threat in South Aceh, Indonesia. This study aimed to evaluate the effectiveness of the DHF control program at Lhok Bengkuang Health Center using input, process, output, outcome indicators. A descriptive qualitative study was conducted from December 2024 to January 2025. Data were collected through in-depth interviews with officers from the South Aceh Health Office, the health center chief, program coordinators, and affected community members. Thematic analysis followed Miles and Huberman’s approach. Triangulation and member checking ensured data validity. DHF cases declined from 22 in 2023 to 7 in 2024. Control activities included source reduction (PSN), larviciding, fogging, health education, epidemiological investigations, and vector surveys. However, the Larvae Free Index (ABJ) remained below the national target of 95%. This indicates partial effectiveness, constrained by limited entomology staff and inadequate personal protective equipment for fogging. Strengthening resources and aligning local implementation with national standards are essential to sustain progress. The DHF control program effectively reduced cases but requires reinforced human resources, adequate equipment, and improved community engagement to meet national targets